2020
DOI: 10.1002/glia.23797
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation: A mechanism for sustained alteration of KIR4.1 expression following central nervous system insult

Abstract: Kir4.1, a glial-specific inwardly rectifying potassium channel, is implicated in astrocytic maintenance of K + homeostasis. Underscoring the role of Kir4.1 in central nervous system (CNS) functioning, genetic mutations in KCNJ10, the gene which encodes Kir4.1, causes seizures, ataxia and developmental disability in humans.Kir4.1 protein and mRNA loss are consistently observed in CNS injury and neurological diseases linked to hyperexcitability and neuronal dysfunction, leading to the notion that Kir4.1 represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 95 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…In a recent study, Boni et al (2020) showed that DNA methylation can bidirectionally modulate transcription of the gene KCNJ10 representing "a targetable molecular mechanism for the restoring astroglial Kir4.1 expression after central nervous system (CNS) insult. " Therefore, DNA hypo-or hypermethylation of candidate genes in astrocytes might be a promising genetic targets for therapeutic intervention of epileptogenesis (Williams-Karnesky et al, 2013).…”
Section: Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, Boni et al (2020) showed that DNA methylation can bidirectionally modulate transcription of the gene KCNJ10 representing "a targetable molecular mechanism for the restoring astroglial Kir4.1 expression after central nervous system (CNS) insult. " Therefore, DNA hypo-or hypermethylation of candidate genes in astrocytes might be a promising genetic targets for therapeutic intervention of epileptogenesis (Williams-Karnesky et al, 2013).…”
Section: Dna Methylationmentioning
confidence: 99%
“…In animal models of structural epilepsy (i.e., induced by injections of pentilentetrazol, PTZ or electrical stimulation of hippocampus) astrocyte swelling was observed through specific targeting of AQP4 or Kir4.1 (see Murphy et al, 2017 ). Genetic mutations in the gene KCNJ10, which encodes Kir4.1, is known to cause seizures in humans (see Boni et al, 2020 ).…”
Section: The Role Of Astrocytes In Structural/metabolic/infectious/im...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported the upregulation of astroglia’s potassium channel gene ( Kir4.1 or KCNJ10 ) and reduced GLT-1 ( SLC1A2 ) activity (which removes ~90% of extracellular/synapse glutamate) and increased neuronal bursting activity of the lateral habenula as key factors in the induction of depression-like behaviors [ 68 , 69 ]. A recent study revealed that DNA methylation regulates KCNJ10 expression in astrocytes [ 74 ]. Aberrant DNA methylation of NMDAR (more specifically, the hypermethylation of the GRIN2A subunit) was also reported in the hippocampus and prefrontal cortex of MDD patients [ 76 ].…”
Section: Astroglia Pathology and Dysfunction In Depressionmentioning
confidence: 99%
“…Lithium can improve the microenvironment in the spinal cord and promote the regeneration and survival of motor neurons [ 90 ]. Lithium chloride can boost the secretion of brain-derived neurotrophic factor (BDNF) in the axons of motor neurons following spinal cord injury [ 91 , 92 ]. Lithium chloride can also help restore the function of the blood–spinal cord barrier after a spinal cord injury [ 93 ].…”
Section: Lithium and Cellular Biology Of Scimentioning
confidence: 99%